DEVELOPMENT OF WEB-BASED LEARNING MEDIA ON NERVOUS SYSTEM MATERIALS FOR HIGH SCHOOL STUDENTS - Ditania Larasati; Hasruddin, Hasruddin (Sindoro: Cendikia Pendidikan, 2024)
Today's teachers are facing students who are no strangers to the digital world. Digital technologies that are developing are learning media, which can be used in education, such as smartphones and others. Therefore, the rapid development of digital learning influences the learning process both in the classroom and outside the classroom. This study aims to determine responses to the feasibility of web-based learning media. This type of research is research and development. Data were analyzed with quantitative description. The research instruments used were questionnaires. The results found that this web-based learning media, based on the results obtained, according to the material experts' feasibility of using web Learning media, reached an assessment score of 95%, with a very valid Achievement category. In comparison, according to media experts, the feasibility of using web Learning media reached an assessment score of 88%, with a very valid Achievement category. The response given by 36 Class XI students of Baitul Aziz Deli Serdang Private High School showed a positive response such as motivating students to learn the web flexibly so that an overall score of 88% was obtained in the very good category. Teacher responses to web-based learning media also showed a positive response, such as media (web) which was used to facilitate teachers in giving assignments so as to obtain an assessment score of 75% in the good category. The response of students and teachers is useful to know the learning process in utilizing internet media and material delivery and knowing the feasibility of the web media used